ANALISIS PENGAKTIVAN NEUTRON - Soenarjo, Sunarhadijoso (Jurnal Radioisotop dan Radiofarmaka, 2008)
NEUTRON ACT IVATION ANALYSIS. Neutron Activation Analysis (NAA) is anelement analysis based on radioactivity characters induced by thermal neutron irradiation on target nucleus. This technique is one of the utilizations of nuclear technique in the field of chemical analysis. As compared to the non-nuclear technique based analytical method, the NAA can be superior although it can only be performed in certain analytical chemistry laboratory due to the requirement and regulation on radiation protection. The presented paper is to give brief introduction on basic principle, grouping, methodology as well as data interpretation and calculation of the NAA method. Some important aspects in connection with implementation of NAA are also discussed. In general, this paper is expected to give positive insight and understanding on the application ofnuclear techniques in the daily life, especially concerning to principle, procedure and data interpretation of NAA.keywords: Neutron activation analysis, application of nuclear techniques, radioactivity, yspectrometry,Kayzero method.